Kajian Kinetika Pengaruh Lama Penyimpanan Terhadap Kadar Vitamin C Pada Buah Apel Malang (Malus Sylvestris) - Anjar Purba Asmara; Hanik Khuriana Amungkasi (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2019)
An analysis for determining kinetics of effect of varied shelf-life time to the level of vitamin C in Malus sylvestris fruits has been conducted. It has used fresh apple Malang (M. sylvestris) from Batu (East Java) at their harvest time with the same size and color as the subject of the research. Therefore, the fruits were stored in room temperature and kept away from direct sunlight for 0, 1, 2, and 3 days. The fruits were extracted by using a juice blending technique with aquadest as the solvent. An iodimetric titration has been used to determine the effect of the varied storage time to the level of vitamin C in the samples. The result shows that the average value of vitamin C level in M. sylvestris stored in 0, 1, 2, and 3 days as much as 2.3904 mg/50g; 2.1073 mg/50g; 2.06695 mg/50g; and 1.9860 mg/50g, respectively. Statistic analysis of ANAVA-A and t-test confirms that there are significant differences between the level of vitamin C of M. sylvestris stored in 0, 1, 2, and 3 days. The conclusion about the kinetics of ascorbic acid degradation of M. sylvestris at 27 0C states three expressions as following as: the reaction is a second order reaction, the constants of reaction rate is 2.65 x 10-2 L(mol.days)-1, the half life is 15.786 days, and kinetics model for the reaction is C = (0.0265t + 1/C0)-1.